The Influence of Talking Stick Learning Models on Students’ Mathematics Learning Motivation at Class X MAN 1 Padangsidimpuan - Rahma Hayati Siregar; Marhamni Ritonga (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2022)
This research is motivated by students' low motivation to learn mathematics, this is influenced by many factors, one of which is the learning model factor provided by the teacher. A learning model that creates a meaningful learning process environment and prioritizes the emergence of motivation to learn mathematics, one of which is the talking stick learning model. So the purpose of this research is to find out the influence of the talking stick learning model on the motivation to learn mathematics for students in class X MAN 1 Padangsidimpuan. This research is a quantitative research with Quasi-experimental method, a type of experimental design quasi experimental design method with the type of one-shot case study design with a sample of class X MIA-1 students totaling 18 people with purposive sampling technique. The data analysis used is descriptive and inferential statistical formulas, namely normality and homogeneity tests and hypothesis tests with one sample t-test. In accordance with hypothesis testing using the one Sample t-test test obtained a calculated price price = 45.249 and a 2-tailed sig value = 0.000, then according to the basis of decision making in the t Test, it can be concluded that H0 is rejected and Ha is accepted at a significance level of 5% (α = 0.05) this shows that there is a significant influence from the application of the Talking Stick learning model on the Students’ Motivation in Learning Mathematics at Class X MAN 1 Padangsidimpuan.